EDUCATION SYSTEM, HUMAN CAPITAL AND ECONOMIC DEVELOPMENT - Salimov Baxtiyor Tadjiyevich (European Science Publishing, 2025)
The article covers the issues of improving the knowledge and professional level of training of personnel for small businesses engaged in innovative activities, assessment of the education system, a systematic approach to improving the quality of education, the role of the education market in improving the quality of the education system, the use of the capabilities of the non-state education system in improving the quality of education and developed recommendations for improving the quality of education in Uzbekistan.
Keywords: Small business, professional level, innovative activities, education system, bachelor, master's degree, strategic plan, human capital, education market, organization of higher education.